Academics Telecommuting in Open and Distance Education Universities: Issues, challenges, and opportunities - Ng, Cheuk Fan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2006)
Research in distance and online education has focused on how to improve students’ learning and support services. Faculty satisfaction, as one of the five pillars in Sloan-Consortium’s quality framework for online education, has received less attention in research. Besides online teaching, little research has examined the experiences of academics working in institutions where the faculty is dispersed geographically. Outside the academy, teleworking or telecommuting has become quite popular in recent years. Most research to-date has been conducted in information technology-related corporations and government departments, but hardly any in post-secondary educational institutions. Drawing on a literature review of research in telecommuting or teleworking, this paper discusses the potential benefits and drawbacks of telecommuting for academics and their families, and the potential opportunities for – and challenges faced – by their distance and online education institutions.